1977
DOI: 10.1177/106002807701100401
|View full text |Cite
|
Sign up to set email alerts
|

Physical Assessment and the Clinical Pharmacist

Abstract: This article introduces a series of articles on physical assessment and the clinical pharmacist. The primary objective of the articles is to present basic knowledge and methods of physical assessment used to monitor drug effect. A post-test based on the competency objectives will be included in a future issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The concept of pharmacists using PE skills in practice can be traced back to the 1970s, 9 but subsequent surveys have demonstrated that most pharmacists do not routinely use PE to monitor their patients. 7–8 More recently, several articles have been published advocating for pharmacists to perform PE, from the perspective of both improved patient care and expanded scope of practice.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of pharmacists using PE skills in practice can be traced back to the 1970s, 9 but subsequent surveys have demonstrated that most pharmacists do not routinely use PE to monitor their patients. 7–8 More recently, several articles have been published advocating for pharmacists to perform PE, from the perspective of both improved patient care and expanded scope of practice.…”
Section: Introductionmentioning
confidence: 99%
“…After the first Delphi round, 20 PE tests yielded consensus to either include 13 or exclude 7 them from entry-to-practice pharmacy programs ( Table 2 ). The second round led to an agreement on 7 additional PE tests to either include 2 or exclude 5 from pharmacy programs. Twenty-two PE tests remained with no agreement after 2 Delphi rounds.…”
Section: Resultsmentioning
confidence: 99%
“…1 Following in the footsteps of other provinces, Quebec pharmacists conducting their medical history interview can now perform physical examination (PE) to complete their data collection. 1 Although the concept of pharmacists performing PE is not novel, 2 this professional activity provokes a wide range of reactions in the pharmacy community, from enthusiasm to skepticism to incomprehension. 3 Traditionally, PE was performed by other health care professionals, such as physicians, but as pharmacists' expertise is expanding to include new professional activities, many pharmacists consider PE to be an essential skill.…”
Section: Introductionmentioning
confidence: 99%
“…This study provides insight into the opinions of pharmacists, nonpharmacist health care providers and the public on pharmacists incorporating physical assessment into their practice. Although the concept of physical assessments performed by a pharmacist is not new, 15 it remains an unusual concept to many. It was therefore not surprising that most nonpharmacist health care providers and the public have not observed pharmacists using these skills.…”
Section: Discussionmentioning
confidence: 99%